(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
ABSTRACT This article analyzes how social media influences language and identity in today's world. It explores the impact of online platforms on language development, the emergence of new communication styles, and the mixing of regional dialects. Additionally, the study examines how social media shapes individual and group identities, influencing cultural norms and self-expression. The research highlights both the positive and negative aspects of digital communication on modern language and identity.